Avian influenza virus directly infects human natural killer cells and inhibits cell activity - Mao, Huawei (Virol Sin, 2017)
Natural killer (NK) cell is a key component of innate immunity and plays an important role in host defense against virus infection by directly destroying infected cells. Influenza is a respiratory disease transmitted in the early phase of virus infection. Evasion of host innate immunity including NK cells is critical for the virus to expand and establish a successful acute infection. Previously, we showed that human influenza H1N1 virus infects NK cells and induces cell apoptosis, as well as inhibits NK cell activity. In this study, we further demonstrated that avian influenza virus also directly targeted NK cells as an immunoevasion strategy. The avian virus infected human NK cells and induced cell apoptosis. In addition, avian influenza virion and HA protein inhibited NK cell cytotoxicity. This novel strategy has obvious advantages for avian influenza virus, allowing the virus sufficient time to expand and subsequent spread before the onset of the specific immune response. Our findings provide an important clue for the immunopathogenesis of avian influenza, and also suggest that direct targeting NK cells may be a common strategy used by both human and avian influenza viruses to evade NK cell immunity. [Image: see text]